Situation 15.6.1. In the following we will consider ring maps

where we assume $A' \to A$ is surjective with kernel $I$. In this situation we set $B' = B \times _ A A'$ to obtain a cartesian square

In this section we discuss fibre products in the following situation.

Situation 15.6.1. In the following we will consider ring maps

\[ \xymatrix{ B \ar[r] & A & A' \ar[l] } \]

where we assume $A' \to A$ is surjective with kernel $I$. In this situation we set $B' = B \times _ A A'$ to obtain a cartesian square

\[ \xymatrix{ A & A' \ar[l] \\ B \ar[u] & B' \ar[l] \ar[u] } \]

Lemma 15.6.2. In Situation 15.6.1 we have

\[ \mathop{\mathrm{Spec}}(B') = \mathop{\mathrm{Spec}}(B) \amalg _{\mathop{\mathrm{Spec}}(A)} \mathop{\mathrm{Spec}}(A') \]

as topological spaces.

**Proof.**
Since $B' = B \times _ A A'$ we obtain a commutative square of spectra, which induces a continuous map

\[ can : \mathop{\mathrm{Spec}}(B) \amalg _{\mathop{\mathrm{Spec}}(A)} \mathop{\mathrm{Spec}}(A') \longrightarrow \mathop{\mathrm{Spec}}(B') \]

as the source is a pushout in the category of topological spaces (which exists by Topology, Section 5.29).

To show the map $can$ is surjective, let $\mathfrak q' \subset B'$ be a prime ideal. If $I \subset \mathfrak q'$ (here and below we take the liberty of considering $I$ as an ideal of $B'$ as well as an ideal of $A'$), then $\mathfrak q'$ corresponds to a prime ideal of $B$ and is in the image. If not, then pick $h \in I$, $h \not\in \mathfrak q'$. In this case $B_ h = A_ h = 0$ and the ring map $B'_ h \to A'_ h$ is an isomorphism, see Lemma 15.5.3. Thus we see that $\mathfrak q'$ corresponds to a unique prime ideal $\mathfrak p' \subset A'$ which does not contain $I$.

Since $B' \to B$ is surjective, we see that $can$ is injective on the summand $\mathop{\mathrm{Spec}}(B)$. We have seen above that $\mathop{\mathrm{Spec}}(A') \to \mathop{\mathrm{Spec}}(B')$ is injective on the complement of $V(I) \subset \mathop{\mathrm{Spec}}(A')$. Since $V(I) \subset \mathop{\mathrm{Spec}}(A')$ is exactly the image of $\mathop{\mathrm{Spec}}(A) \to \mathop{\mathrm{Spec}}(A')$ a trivial set theoretic argument shows that $can$ is injective.

To finish the proof we have to show that $can$ is open. To do this, observe that an open of the pushout is of the form $V \amalg U'$ where $V \subset \mathop{\mathrm{Spec}}(B)$ and $U' \subset \mathop{\mathrm{Spec}}(A')$ are opens whose inverse images in $\mathop{\mathrm{Spec}}(A)$ agree. Let $v \in V$. We can find a $g \in B$ such that $v \in D(g) \subset V$. Let $f \in A$ be the image. Pick $f' \in A'$ mapping to $f$. Then $D(f') \cap U' \cap V(I) = D(f') \cap V(I)$. Hence $V(I) \cap D(f')$ and $D(f') \cap (U')^ c$ are disjoint closed subsets of $D(f') = \mathop{\mathrm{Spec}}(A'_{f'})$. Write $(U')^ c = V(J)$ for some ideal $J \subset A'$. Since $A'_{f'} \to A'_{f'}/IA'_{f'} \times A'_{f'}/JA'_{f'}$ is surjective by the disjointness just shown, we can find an $a'' \in A'_{f'}$ mapping to $1$ in $A'_{f'}/IA'_{f'}$ and mapping to zero in $A'_{f'}/JA'_{f'}$. Clearing denominators, we find an element $a' \in J$ mapping to $f^ n$ in $A$. Then $D(a'f') \subset U'$. Let $h' = (g^{n + 1}, a'f') \in B'$. Since $B'_{h'} = B_{g^{n + 1}} \times _{A_{f^{n + 1}}} A'_{a'f'}$ by a previously cited lemma, we see that $D(h')$ pulls back to an open neighbourhood of $v$ in the pushout, i.e., the image of $V \amalg U'$ contains an open neighbourhood of the image of $v$. We omit the (easier) proof that the same thing is true for $u' \in U'$ with $u' \not\in V(I)$. $\square$

Lemma 15.6.3. In Situation 15.6.1 if $B \to A$ is integral, then $B' \to A'$ is integral.

**Proof.**
Let $a' \in A'$ with image $a \in A$. Let $x^ d + b_1 x^{d - 1} + \ldots + b_ d$ be a monical polynomial with coefficients in $B$ satisfied by $a$. Choose $b'_ i \in B'$ mapping to $b_ i \in B$ (possible). Then $(a')^ d + b'_1 (a')^{d - 1} + \ldots + b'_ d$ is in the kernel of $A' \to A$. Since $\mathop{\mathrm{Ker}}(B' \to B) = \mathop{\mathrm{Ker}}(A' \to A)$ we can modify our choice of $b'_ d$ to get $(a')^ d + b'_1 (a')^{d - 1} + \ldots + b'_ d = 0$ as desired.
$\square$

In Situation 15.6.1 we'd like to understand $B'$-modules in terms of modules over $A'$, $A$, and $B$. In order to do this we consider the functor (where the fibre product of categories as constructed in Categories, Example 4.31.3)

15.6.3.1

\begin{equation} \label{more-algebra-equation-functor} \text{Mod}_{B'} \longrightarrow \text{Mod}_ B \times _{\text{Mod}_ A} \text{Mod}_{A'},\quad L' \longmapsto (L' \otimes _{B'} B, L' \otimes _{B'} A', can) \end{equation}

where $can$ is the canonical identification $L' \otimes _{B'} B \otimes _ B A = L' \otimes _{B'} A' \otimes _{A'} A$. In the following we will write $(N, M', \varphi )$ for an object of the right hand side, i.e., $N$ is a $B$-module, $M'$ is an $A'$-module and $\varphi : N \otimes _ B A \to M' \otimes _{A'} A$ is an isomorphism. However, it is often more convenient think of $\varphi $ as a $B$-linear map $\varphi : N \to M'/IM'$ which induces an isomorphism $N \otimes _ B A \to M' \otimes _{A'} A = M'/IM'$.

Lemma 15.6.4. In Situation 15.6.1 the functor (15.6.3.1) has a right adjoint, namely the functor

\[ F : (N, M', \varphi ) \longmapsto N \times _{\varphi , M} M' \]

where $M = M'/IM'$. Moreover, the composition of $F$ with (15.6.3.1) is the identity functor on $\text{Mod}_ B \times _{\text{Mod}_ A} \text{Mod}_{A'}$. In other words, setting $N' = N \times _{\varphi , M} M'$ we have $N' \otimes _{B'} B = N$ and $N' \otimes _{B'} A' = M'$.

**Proof.**
The adjointness statement follows from the more general Lemma 15.5.4. To prove the final assertion, recall that $B' = B \times _ A A'$ and $N' = N \times _{\varphi , M} M'$ and extend these equalities to

\[ \vcenter { \xymatrix{ A & A' \ar[l] & I \ar[l] \\ B \ar[u] & B' \ar[l] \ar[u] & J \ar[l] \ar[u] } } \quad \text{and}\quad \vcenter { \xymatrix{ M & M' \ar[l] & K \ar[l] \\ N \ar[u]_\varphi & N' \ar[l] \ar[u] & L \ar[l] \ar[u] } } \]

where $I, J, K, L$ are the kernels of the horizontal maps of the original diagrams. We present the proof as a sequence of observations:

$K = IM'$ (see statement lemma),

$B' \to B$ is surjective with kernel $J$ and $J \to I$ is bijective,

$N' \to N$ is surjective with kernel $L$ and $L \to K$ is bijective,

$JN' \subset L$,

$\mathop{\mathrm{Im}}(N \to M)$ generates $M$ as an $A$-module (because $N \otimes _ B A = M$),

$\mathop{\mathrm{Im}}(N' \to M')$ generates $M'$ as an $A'$-module (because it holds modulo $K$ and $L$ maps isomorphically to $K$),

$JN' = L$ (because $L \cong K = I M'$ is generated by images of elements $x n'$ with $x \in I$ and $n' \in N'$ by the previous statement),

$N' \otimes _{B'} B = N$ (because $N = N'/L$, $B = B'/J$, and the previous statement),

there is a map $\gamma : N' \otimes _{B'} A' \to M'$,

$\gamma $ is surjective (see above),

the kernel of the composition $N' \otimes _{B'} A' \to M' \to M$ is generated by elements $l \otimes 1$ and $n' \otimes x$ with $l \in K$, $n' \in N'$, $x \in I$ (because $M = N \otimes _ B A$ by assumption and because $N' \to N$ and $A' \to A$ are surjective with kernels $L$ and $I$),

any element of $N' \otimes _{B'} A'$ in the submodule generated by the elements $l \otimes 1$ and $n' \otimes x$ with $l \in L$, $n' \in N'$, $x \in I$ can be written as $l \otimes 1$ for some $l \in L$ (because $J$ maps isomorphically to $I$ we see that $n' \otimes x = n'x \otimes 1$ in $N' \otimes _{B'} A'$; similarly $x n' \otimes a' = n' \otimes xa' = n'(xa') \otimes 1$ in $N' \otimes _{B'} A'$ when $n' \in N'$, $x \in J$ and $a' \in A'$; since we have seen that $JN' = L$ this proves the assertion),

the kernel of $\gamma $ is zero (because by (10) and (11) any element of the kernel is of the form $l \otimes 1$ with $l \in L$ which is mapped to $l \in K \subset M'$ by $\gamma $).

This finishes the proof. $\square$

Lemma 15.6.5. In the situation of Lemma 15.6.4 for a $B'$-module $L'$ the adjunction map

\[ L' \longrightarrow (L' \otimes _{B'} B) \times _{(L' \otimes _{B'} A)} (L' \otimes _{B'} A') \]

is surjective but in general not injective.

**Proof.**
As in the proof of Lemma 15.6.4 let $J \subset B'$ be the kernel of the map $B' \to B$. Then $L' \otimes _{B'} B = L'/JL'$. Hence to prove surjectivity it suffices to show that elements of the form $(0, z)$ of the fibre product are in the image of the map of the lemma. The kernel of the map $L' \otimes _{B'} A' \to L' \otimes _{B'} A$ is the image of $L' \otimes _{B'} I \to L' \otimes _{B'} A'$. Since the map $J \to I$ induced by $B' \to A'$ is an isomorphism the composition

\[ L' \otimes _{B'} J \to L' \to (L' \otimes _{B'} B) \times _{(L' \otimes _{B'} A)} (L' \otimes _{B'} A') \]

induces a surjection of $L' \otimes _{B'} J$ onto the set of elements of the form $(0, z)$. To see the map is not injective in general we present a simple example. Namely, take a field $k$, set $B' = k[x, y]/(xy)$, $A' = B'/(x)$, $B = B'/(y)$, $A = B'/(x, y)$ and $L' = B'/(x - y)$. In that case the class of $x$ in $L'$ is nonzero but is mapped to zero under the displayed arrow. $\square$

Lemma 15.6.6. In Situation 15.6.1 let $(N_1, M'_1, \varphi _1) \to (N_2, M'_2, \varphi _2)$ be a morphism of $\text{Mod}_ B \times _{\text{Mod}_ A} \text{Mod}_{A'}$ with $N_1 \to N_2$ and $M'_1 \to M'_2$ surjective. Then

\[ N_1 \times _{\varphi _1, M_1} M'_1 \to N_2 \times _{\varphi _2, M_2} M'_2 \]

where $M_1 = M'_1/IM'_1$ and $M_2 = M'_2/IM'_2$ is surjective.

**Proof.**
Pick $(x_2, y_2) \in N_2 \times _{\varphi _2, M_2} M'_2$. Choose $x_1 \in N_1$ mapping to $x_2$. Since $M'_1 \to M_1$ is surjective we can find $y_1 \in M'_1$ mapping to $\varphi _1(x_1)$. Then $(x_1, y_1)$ maps to $(x_2, y'_2)$ in $N_2 \times _{\varphi _2, M_2} M'_2$. Thus it suffices to show that elements of the form $(0, y_2)$ are in the image of the map. Here we see that $y_2 \in IM'_2$. Write $y_2 = \sum t_ i y_{2, i}$ with $t_ i \in I$. Choose $y_{1, i} \in M'_1$ mapping to $y_{2, i}$. Then $y_1 = \sum t_ iy_{1, i} \in IM'_1$ and the element $(0, y_1)$ does the job.
$\square$

Lemma 15.6.7. Let $A, A', B, B', I, M, M', N, \varphi $ be as in Lemma 15.6.4. If $N$ finite over $B$ and $M'$ finite over $A'$, then $N' = N \times _{\varphi , M} M'$ is finite over $B'$.

**Proof.**
We will use the results of Lemma 15.6.4 without further mention. Choose generators $y_1, \ldots , y_ r$ of $N$ over $B$ and generators $x_1, \ldots , x_ s$ of $M'$ over $A'$. Using that $N = N' \otimes _{B'} B$ and $B' \to B$ is surjective we can find $u_1, \ldots , u_ r \in N'$ mapping to $y_1, \ldots , y_ r$ in $N$. Using that $M' = N' \otimes _{B'} A'$ we can find $v_1, \ldots , v_ t \in N'$ such that $x_ i = \sum v_ j \otimes a'_{ij}$ for some $a'_{ij} \in A'$. In particular we see that the images $\overline{v}_ j \in M'$ of the $v_ j$ generate $M'$ over $A'$. We claim that $u_1, \ldots , u_ r, v_1, \ldots , v_ t$ generate $N'$ as a $B'$-module. Namely, pick $\xi \in N'$. We first choose $b'_1, \ldots , b'_ r \in B'$ such that $\xi $ and $\sum b'_ i u_ i$ map to the same element of $N$. This is possible because $B' \to B$ is surjective and $y_1, \ldots , y_ r$ generate $N$ over $B$. The difference $\xi - \sum b'_ i u_ i$ is of the form $(0, \theta )$ for some $\theta $ in $IM'$. Say $\theta $ is $\sum t_ j\overline{v}_ j$ with $t_ j \in I$. As $J = \mathop{\mathrm{Ker}}(B' \to B)$ maps isomorphically to $I$ we can choose $s_ j \in J \subset B'$ mapping to $t_ j$. Because $N' = N \times _{\varphi , M} M'$ it follows that $\xi = \sum b'_ i u_ i + \sum s_ j v_ j$ as desired.
$\square$

Lemma 15.6.8. With $A, A', B, B', I$ as in Situation 15.6.1.

Let $(N, M', \varphi )$ be an object of $\text{Mod}_ B \times _{\text{Mod}_ A} \text{Mod}_{A'}$. If $M'$ is flat over $A'$ and $N$ is flat over $B$, then $N' = N \times _{\varphi , M} M'$ is flat over $B'$.

If $L'$ is a flat $B'$-module, then $L' = (L \otimes _{B'} B) \times _{(L \otimes _{B'} A)} (L \otimes _{B'} A')$.

The category of flat $B'$-modules is equivalent to the full subcategory of $\text{Mod}_ B \times _{\text{Mod}_ A} \text{Mod}_{A'}$ consisting of triples $(N, M', \varphi )$ with $N$ flat over $B$ and $M'$ flat over $A'$.

**Proof.**
In the proof we will use Lemma 15.6.4 without further mention.

Proof of (1). Set $J = \mathop{\mathrm{Ker}}(B' \to B)$. This is an ideal of $B'$ mapping isomorphically to $I = \mathop{\mathrm{Ker}}(A' \to A)$. Let $\mathfrak b' \subset B'$ be an ideal. We have to show that $\mathfrak b' \otimes _{B'} N' \to N'$ is injective, see Algebra, Lemma 10.39.5. We know that

\[ \mathfrak b'/(\mathfrak b' \cap J) \otimes _{B'} N' = \mathfrak b'/(\mathfrak b' \cap J) \otimes _ B N \to N \]

is injective as $N$ is flat over $B$. As $\mathfrak b' \cap J \to \mathfrak b' \to \mathfrak b'/(\mathfrak b' \cap J) \to 0$ is exact, we conclude that it suffices to show that $(\mathfrak b' \cap J) \otimes _{B'} N' \to N'$ is injective. Thus we may assume that $\mathfrak b' \subset J$. Next, since $J \to I$ is an isomorphism we have

\[ J \otimes _{B'} N' = I \otimes _{A'} A' \otimes _{B'} N' = I \otimes _{A'} M' \]

which maps injectively into $M'$ as $M'$ is a flat $A'$-module. Hence $J \otimes _{B'} N' \to N'$ is injective and we conclude that $\text{Tor}_1^{B'}(B'/J, N') = 0$, see Algebra, Remark 10.75.9. Thus we may apply Algebra, Lemma 10.99.8 to $N'$ over $B'$ and the ideal $J$. Going back to our ideal $\mathfrak b' \subset J$, let $\mathfrak b' \subset \mathfrak b'' \subset J$ be the smallest ideal whose image in $I$ is an $A'$-submodule of $I$. In other words, we have $\mathfrak b'' = A' \mathfrak b'$ if we view $J = I$ as $A'$-module. Then $\mathfrak b''/\mathfrak b'$ is killed by $J$ and we get a short exact sequence

\[ 0 \to \mathfrak b' \otimes _{B'} N' \to \mathfrak b'' \otimes _{B'} N' \to \mathfrak b''/\mathfrak b' \otimes _{B'} N' \to 0 \]

by the vanishing of $\text{Tor}_1^{B'}(\mathfrak b''/\mathfrak b', N')$ we get from the application of the lemma. Thus we may replace $\mathfrak b'$ by $\mathfrak b''$. In particular we may assume $\mathfrak b'$ is an $A'$-module and maps to an ideal of $A'$. Then

\[ \mathfrak b' \otimes _{B'} N' = \mathfrak b' \otimes _{A'} A' \otimes _{B'} N' = \mathfrak b' \otimes _{A'} M' \]

This tensor product maps injectively into $M'$ by our assumption that $M'$ is flat over $A'$. We conclude that $\mathfrak b' \otimes _{B'} N' \to N' \to M'$ is injective and hence the first map is injective as desired.

Proof of (2). This follows by tensoring the short exact sequence $0 \to B' \to B \oplus A' \to A \to 0$ with $L'$ over $B'$.

Proof of (3). Immediate consequence of (1) and (2). $\square$

Lemma 15.6.9. Let $A, A', B, B', I$ be as in Situation 15.6.1. The category of finite projective $B'$-modules is equivalent to the full subcategory of $\text{Mod}_ B \times _{\text{Mod}_ A} \text{Mod}_{A'}$ consisting of triples $(N, M', \varphi )$ with $N$ finite projective over $B$ and $M'$ finite projective over $A'$.

**Proof.**
Recall that a module is finite projective if and only if it is finitely presented and flat, see Algebra, Lemma 10.78.2. Using Lemmas 15.6.8 and 15.6.7 we reduce to showing that $N' = N \times _{\varphi , M} M'$ is a $B'$-module of finite presentation if $N$ finite projective over $B$ and $M'$ finite projective over $A'$.

By Lemma 15.6.7 the module $N'$ is finite over $B'$. Choose a surjection $(B')^{\oplus n} \to N'$ with kernel $K'$. By base change we obtain maps $B^{\oplus n} \to N$, $(A')^{\oplus n} \to M'$, and $A^{\oplus n} \to M$ with kernels $K_ B$, $K_{A'}$, and $K_ A$. There is a canonical map

\[ K' \longrightarrow K_ B \times _{K_ A} K_{A'} \]

On the other hand, since $N' = N \times _{\varphi , M} M'$ and $B' = B \times _ A A'$ there is also a canonical map $K_ B \times _{K_ A} K_{A'} \to K'$ inverse to the displayed arrow. Hence the displayed map is an isomorphism. By Algebra, Lemma 10.5.3 the modules $K_ B$ and $K_{A'}$ are finite. We conclude from Lemma 15.6.7 that $K'$ is a finite $B'$-module provided that $K_ B \to K_ A$ and $K_{A'} \to K_ A$ induce isomorphisms $K_ B \otimes _ B A = K_ A = K_{A'} \otimes _{A'} A$. This is true because the flatness assumptions implies the sequences

\[ 0 \to K_ B \to B^{\oplus n} \to N \to 0 \quad \text{and}\quad 0 \to K_{A'} \to (A')^{\oplus n} \to M' \to 0 \]

stay exact upon tensoring, see Algebra, Lemma 10.39.12. $\square$

Your email address will not be published. Required fields are marked.

In your comment you can use Markdown and LaTeX style mathematics (enclose it like `$\pi$`

). A preview option is available if you wish to see how it works out (just click on the eye in the toolbar).

Unfortunately JavaScript is disabled in your browser, so the comment preview function will not work.

All contributions are licensed under the GNU Free Documentation License.

## Comments (0)